Infusión de hojas de moringa oleífera (moringa) e hibiscus sabdariffa (flor de jamaica) - Burgos Dias, Karina Alexandra; Reyes Jara, Marjorie Gabriela (Machala : Universidad Técnica de Machala, 2018)
Moringa oleífera Lam (moringa) is a tropical plant used with medicinal and food purposes. The interest of this plant as a functional food and as a source of nutraceuticals is widely disseminated worldwide, with leaves and seeds being the most widely used due to the content of bioactive compounds. Taking into consideration the benefits that it reports, the objective of the research was to design an infusion combining the leaves of M. oleífera (moringa) with the chalices of H. sabdariffa (Jamaica), taking advantage of the nutrient and bioactive content of these materials vegetable bonuses. To do this, a physical-chemical analysis of crude drugs was performed, obtaining 5.11% residual moisture in M. oleífera and 6.92% for H. sabdariffa. The total ashes were determined in both raw materials, finding 9.46% and 4.92% of inorganic matter. When total ash was treated with 10% HCl, these values were reduced to 3.39% and 1.12% for moringa and jamaica, respectively. The protein content was only determined for moringa, through the Bradford method, being 27.67 mg/100g of dry drug. The analysis of the mineral content determined the presence of the macronutrients N, P, K and Ca, resulting in higher percentages obtained for moringa, in all cases. With regard to quantified micronutrients (Mg, Zn, Cu, Fe, Mn, Na and B), the presence of Fe (114.9 ppm) in moringa stands out, a result referred by other authors for said biomass. The determination of As and Pb in both drugs yielded values lower than 0.005 and 0.09, respectively, in the same way the microbiological analysis was performed; both parameters comply with the limits established to guarantee the consumption of both drugs.
Moringa oleífera Lam (moringa) es una planta tropical usada con propósitos medicinales y alimenticios. El interés de esta planta como alimento funcional y como fuente de nutracéuticos, está ampliamente difundido a escala mundial, siendo las hojas y semillas las de mayor utilización por el contenido de compuestos bioactivos. Tomando en consideración los beneficios que la misma reporta, el objetivo de la investigación fue diseñar una infusión combinando las hojas de M. oleífera (moringa) con los cálices de H. sabdariffa (jamaica), aprovechando el contenido de nutrientes y bioactivos de estas materias primas vegetales. Para ello se realizó un análisis físico-químico de las drogas crudas, obteniéndose el 5,11% de humedad residual en M. oleífera y 6,92 % para H. sabdariffa. Se determinaron las cenizas totales en ambas materias primas, encontrándose 9,46% y 4,92% de materia inorgánica. Al ser tratadas las cenizas totales con HCl al 10%, dichos valores se redujeron a 3,39% y 1,12% para la moringa y jamaica, respectivamente. El contenido de proteínas solo fue determinado para la moringa, a través del método de Bradford, siendo de 27,67 mg/100g de droga seca. El análisis del contenido de minerales determinó la presencia de los macronutientes N, P, K y Ca, resultando ser superiores los porcentajes obtenidos para la moringa, en todos los casos. Respecto a los micronutrientes cuantificados (Mg, Zn, Cu, Fe, Mn, Na y B), destaca la presencia de Fe (114,9 ppm) en la moringa, resultado referido por otros autores para dicha biomasa. La determinación de As y Pb en ambas drogas, arrojó valores inferiores a 0,005 y 0,09, respectivamente, de igual manera se realizó el análisis microbiológico; ambos parámetros cumplen con los límites establecidos para avalar el consumo de ambas drogas.
Keywords: MORINGA OLEIFERA; HIBISCUS SABDARIFFA; TE DE HIERBAS; COMPUESTOS FENOLICOS